On the growth of system of entire homogenous polynomials of several complex variables - Hameed, Aseel; A.Hussein, MushtaqShakir (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
In this paper we study the growth of entire functions represented by homogenous polynomials of two complex variables. The characterizations of their order and type have been obtained